Periplasmic Bacterial Biomineralization of Copper Sulfide Nanoparticles. Issue 28 (17th August 2022) - Park, Yeseul; Eyal, Zohar; Pekker, Péter; Chevrier, Daniel M.; Lefèvre, Christopher T.; Arnoux, Pascal; Armengaud, Jean; Monteil, Caroline L.; Gal, Assaf; Pósfai, Mihály; Faivre, Damien
Abstract: Metal sulfides are a common group of extracellular bacterial biominerals. However, only a few cases of intracellular biomineralization are reported in this group, mostly limited to greigite (Fe3 S4 ) in magnetotactic bacteria. Here, a previously unknown periplasmic biomineralization of copper sulfide produced by the magnetotactic bacterium Desulfamplus magnetovallimortis strain BW‐1, a species known to mineralize greigite (Fe3 S4 ) and magnetite (Fe3 O4 ) in the cytoplasm is reported. BW‐1 produces hundreds of spherical nanoparticles, composed of 1–2 nm substructures of a poorly crystalline hexagonal copper sulfide structure that remains in a thermodynamically unstable state. The particles appear to be surrounded by an organic matrix as found from staining and electron microscopy inspection. Differential proteomics suggests that periplasmic proteins, such as a DegP‐like protein and a heavy metal‐binding protein, could be involved in this biomineralization process. The unexpected periplasmic formation of copper sulfide nanoparticles in BW‐1 reveals previously unknown possibilities for intracellular biomineralization that involves intriguing biological control and holds promise for biological metal recovery in times of copper shortage. Abstract : Some bacteria have the capability of forming inorganic nanoparticles in a process called biomineralization. A magnetotactic bacterium is shown here, that can precipitate an unknown type of intracellular copper‐based nanoparticles in the periplasm. The biomineral shows peculiar nanometric sub‐structures, and a potential organic envelope surrounding the particles. The protein analysis points toward a new biomineralization mechanism involved in copper detoxification.